The Critical Efforts of Hazem Al-Qartajani in his Book Minhaj Language and the saddle of writers (Journal of the College of Basic Education, 2022)
When a conversation takes place between students of literature and its critics regarding theoretical criticism and itsHazem Al-Qartajani is one of his prominent leaders, with whom the discussion revolves, and his bold critical views remain.His correct view of poetry, its origins, and methods of constructing it is admired by all because it attracted the theoryCriticism of rhetoricians and critics who preceded him, such as Abu Hilal al-Askari, Abd al-Qaher al-Jurjani, and IbnAl-Atheer, Al-Alawy, Sahib Al-Taraz, and others, as he digested their theories on the origins of literary creativity inthe fields of poetry and prose, but he did not stop at the limits of following, and in the field of apprenticeship, but was able with his mindThe feat is to benefit from the represented Greek criticism